EVALUATION OF MOTOR DEVELOPMENT AND SKILLS IN MINI‐VOLLEYBALL GAME (10‐12 YEARS OLD) - I. S. SOPA; M. POMOHACI (Editura Universitatii Transilvania din Brasov, 2018)
Our study focused on the efficient evaluation process of motor development, technical skills and anthropometric development of a mini‐volleyball team. The research sample was composed of 22 players with aged between 10 and 12 years old that are registered at CSM Bucharest mini‐volleyball team. The battery of anthropometric test evaluated the following indices: height, weight, the length of the superior members, the length of the inferior members, body mass index and wing span. The battery tests for motor and skills evaluation were composed from the following tests: T‐test,Illinois test and some specific test for movement. The research results showed that our team had better performances in agility test and coordination test from the initial test compared with the final test and also we found that players developed their anthropometric parameters. Differences between the final and initial testing among pupils from the group were significant in all motor and anthropometric tests (p <0.05). Conclusions have shown that the research hypothesis was valid, so we can say that inclusion of agility and coordination exercises in our programs can influence in a good way the student's motor performance at this age.